2004
DOI: 10.1177/004051750407400707
|View full text |Cite
|
Sign up to set email alerts
|

Comfort Pressure of the Top Part of Men's Socks

Abstract: In this study, the relation between pressure values and the feeling of pressure of the top part of men's socks (hereafter, the top) is investigated to design and develop socks that provide wearing comfort. Leg size, tensile properties and pressure values of the top are measured, and the pressure feeling is evaluated. When the tops of men's casual socks are stretched to a certain extent this induces stress relaxation and the feeling of pressure changes depending on wearing time. In this study, a certain stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…While pressure measurement systems enable to quantify the force textiles apply on the human body, 3D scans visualize the tissue changes. The ergonomic wearing comfort of men's stockings [1], men's suits [2], bras [3], sportswear [4,5], compression textiles for medical applications [6,7] etc. was examined.…”
Section: Garment Pressure Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…While pressure measurement systems enable to quantify the force textiles apply on the human body, 3D scans visualize the tissue changes. The ergonomic wearing comfort of men's stockings [1], men's suits [2], bras [3], sportswear [4,5], compression textiles for medical applications [6,7] etc. was examined.…”
Section: Garment Pressure Evaluationmentioning
confidence: 99%
“…was examined. Tsujisaka et al (2004), Wang et al (2011) und Dongsheng et al (2003) deployed standard pressure sensors (e.g. PicoPress®, Kikuhime, FlexiForce) or internal developments on the base of pneumatic converters [8][9][10].…”
Section: Garment Pressure Evaluationmentioning
confidence: 99%
“…Pressure applied by the fabric on the body depends on three factors, namely the shape of the body that is supposed to be covered by fabric, fiber type, and fabric design [10]. To achieve the desired properties of garment, predicting the amount of pressure is necessary [11].…”
Section: Introductionmentioning
confidence: 99%
“…1 Most published research on garment pressure has focused on measuring the pressure directly and evaluating relevant subjective sensations, thereby looking for the range of comfort pressure values. [2][3][4] Momata et al 5 and Toshiyuki 6 have found the pressure comfort range of the top part of socks.…”
mentioning
confidence: 99%